Percutaneous Left Atrial Appendage Occlusion: An Emerging Option in Patients with Atrial Fibrillation at High Risk of Bleeding - Giovanni Cimmino; Francesco S. Loffredo; Emanuele Gallinoro; Dario Prozzo; Dario Fabiani; Luigi Cante; Gemma Salerno; Maurizio Cappelli Bigazzi; Paolo Golino (Medicina, 2021)
Atrial fibrillation (AF) is a common cardiac arrhythmia with an estimated prevalence of 1% in the general population. It is associated with an increased risk of ischemic stroke, silent cerebral ischemia, and cognitive impairment. Due to the blood flow stasis and morphology, thrombus formation occurs mainly in the left atrial appendage (LAA), particularly in the setting of nonvalvular AF (NVAF). Previous studies have shown that >90% of emboli related to NVAF originate from the LAA, thus prevention of systemic cardioembolism is indicated. According to the current guidelines, anticoagulant therapy with direct oral anticoagulants (DOACs) or vitamin K antagonists (VKAs), represents the standard of care in AF patients, in order to prevent ischemic stroke and peripheral embolization. Although these drugs are widely used and DOACs have shown, compared to VKAs, non-inferiority for stroke prevention with significantly fewer bleeding complications, some issues remain a matter of debate, including contraindications, side effects, and adherence. An increasing number of patients, indeed, because of high bleeding risk or after experiencing life-threatening bleedings, must take anticoagulants with extreme caution if not contraindicated. While surgical closure or exclusion of LAA has been historically used in patients with AF with contradictory results, in the recent years, a novel procedure has emerged to prevent the cardioembolic stroke in these patients: The percutaneous left atrial appendage occlusion (LAAO). Different devices have been developed in recent years, though not all of them are approved in Europe and some are still under clinical investigation. Currently available devices have shown a significant decrease in bleeding risk while maintaining efficacy in preventing thromboembolism. The procedure can be performed percutaneously through the femoral vein access, under general anesthesia. A transseptal puncture is required to access left atrium and is guided by transesophageal echocardiography (TEE). Evidence from the current literature indicates that percutaneous LAAO represents a safe alternative for those patients with contraindications for long-term oral anticoagulation. This review summarizes scientific evidences regarding LAAO for stroke prevention including clinical indications and an adequate patient selection.